The Effect of Income, Interest Rates, and Quality of Service on Decisions to Granting Credit - DEWI, Ni Putu Emi Kristina; DEWI, I Gusti Ayu Ratih Permata; KAWISANA, Putu Gede Wisnu Permana (Journal of Entrepreneurial and Business Diversity, 2024)
Purpose:Study This aim to know the Influence of Income, Interest Rates, and Quality Service Against Awarding Decision Credit to BPR throughout the Regency Gianyar.Methodology:The magnitude sample used as many as 72 respondents using purposive sampling. All data from the distribution questionnaire was used and analyzed using multiple linear regression and hypothesis testing (t-test and f-test).Findings:Research results show that (1) Income positively influences Award Decision Credit at the BPR of the Regency Gianyar. (2) Interest Rates influential and favorable to Award Decision Credit at the BPR of the Regency Gianyar. (3) Quality Service influential positive to Award Decision Credit at the BPR of the Regency Gianyar.Implication:This study has the influence and impact that: 1) Income influential positive to Award Decision Credit at the BPR of the Regency Gianyar. 2) Interest Rates are influential and favorable to Award Decision Credit at the BPR of the Regency of Gianyar. 3) Quality Service influential positively to Award Decision Credit at the BPR of the Regency Gianyar.